Determination of rate constants for trifluoromethyl radical addition to various alkenes via a practical method. Issue 1 (17th November 2015) - Hartmann, M.; Li, Y.; Studer, A.
Abstract : A simple method for the determination of CF3-radical addition rate constants to various π-acceptors is introduced. Abstract : A simple and practical method for the determination of rate constants for trifluoromethyl radical addition to various alkenes by applying competition kinetics is introduced. In the kinetic experiments the trifluoromethyl radicals are generated in situ from a commercially available hypervalent-iodine-CF3 reagent (Togni-reagent) by SET-reduction with TEMPONa in the presence of TEMPO and a π-acceptor. From the relative ratio of TEMPOCF3 and CF3 -addition product formed, which is readily determined by 19 F-NMR spectroscopy, rate constants for trifluoromethyl radical addition to the π-acceptor can be calculated. The practical method is also applicable to measure rate constants for the addition of other perfluoroalkyl radicals to alkenes as documented for CF3 CF2 -radical addition reactions.